PREJUDICE IS THE FINAL KEY TO EVALUATING EVIDENCE IN CRIMINAL PROCEEDINGS (World Bulletin of Management and Law, 2023)
this article reflects the scientific views and theories regarding the final evaluation of certain evidence by the court, the result of the given evaluation is of decisive importance and serves to ensure its recognition without re-evaluation for other inquiry and investigative bodies and courts. In addition, prejudice has been strengthened as evidence in criminal proceedings. The limits of the application of prejudice, the issues of its use are studied both practically and theoretically